UJI AKTIVITAS EKSTRAK Sargassum crassifolium SEBAGAI ANTIFUNGI Candida albicans - - Triastinurmiatiningsih; Rina Yulianti; Dewi Sugiharti (Universitas Pakuan, 2015)
Sargassum crassifolium is a species that is included in the class Phaeophyceae. This Brown algae is a alginat source manufacturer and contain active compounds include flavonoids, saponins and triterpenoid which function as antibacterial, antiviral and antifungal properties. The purpose of this research is to know the activities of Sargassum crassifolium in inhibiting the growth of Candida albicans and phytochemicals content. The extraction is done using the method of maceration. Test the effectiveness of antifungal performed using diffusion agar method and paper discs. The parameters observed were drag area width. Data was analyzed using Anova with a level of confidence of 95%. The results showed that the average diameter of the drag area extract Sargassum crassifolium is most effective on a 75% concentration of 21.6 mm. Phytochemical analysis shows that Sargassum crassifolium contains the active compounds such as flavonoids, saponins, and triterpenoid.Key words : Sargassum crassifolium, Candida albicans, antifungal